Out-of-band radiation in information processing equipment measurement of communication systems - Kadatskaja, О.; Yerrafiq Muad; Martynchuk, A.; Saburova, S. (ХНУРЕ, 2023)
In work investigating methods for detecting and analyzing OBR, using statistical method for evaluating the quality indicators of developed OBR mitigation methods based on mathematical modeling. Is propose methods of using SDR receivers to detect and analyze electromagnetic emissions and reducing OBR to improve the security of electronic devices can be applied in the field of measurement and in organizing the protection of information systems.
Keywords: using SDR receivers; electromagnetic emissions